(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article reveals the financial mechanisms for effectively attracting foreign investment into the economy: methods, forms, management tools and financial instruments for effectively attracting foreign investment. As a result of the research, the author’s conclusion on the financial mechanism for attracting foreign investment is formed, conclusions and recommendations are given.